Pemberdayaan Kader Kesehatan Pra Lansia dan Lansia Terkait Informasi Penggunaan Obat yang Tepat di Kelurahan Kasin Kota Malang - Sawu, Sirilus Deodatus; Wibowo, Wibowo; One Irawan, Fransisca Elsia (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Knowledge is the level of patient behavior in carrying out treatment and behavior recommended by doctors or others. If a patient has good knowledge regarding the therapy they are undergoing, their compliance will be very good. Pre-elderly and elderly patients are known to have poor compliance levels due to the large number of medications consumed (polypharmacy), fear of side effects, or forgetting to take medication. The purpose of this community service activity is to improve the knowledge and compliance of pre-elderly and elderly health cadres in Kasin Village, Malang City, totaling 25 cadres from 11 RW (neighborhood associations). The method used is providing socialization through PowerPoint media and booklets. Evaluation of measuring the understanding of community service participants by comparing the average pretest and posttest scores. The results of the activity evaluation showed a significant increase in the understanding of health cadres where the average pretest score of 7.32 increased to 9.56 during the posttest. The percentage increase in the average score of 30.6% indicates that the Community Service activity was successful.